Struktur Komunitas Plankton Di Perairan Gosong Tiaka Kabupaten Morowali Provinsi Sulawesi Tengah - Mansyur, Kasim; Tis’in, Tis’in; Safir, Muhammad (Universitas Madako Tolitoli, 2024)
Plankton are important organisms in aquatic ecosystems including marine ecosystems because of their large contribution to primary productivity and consumer abundance. The role of plankton as an important component in maintaining the balance of aquatic ecosystems and providing fishery resources that benefit the surrounding community is the basis for research on the condition of plankton in the waters of Gosong Tiaka. This study aims to assess the species composition and ecological index of plankton in the location. The research location was divided into 5 stations, namely the western part of Gosong Tiaka, northwest of Gosong Tiaka, southwest of Gosong Tiaka and northeast of Gosong Tiaka. The results showed that there were 6 phytoplankton classes and 8 zooplankton classes in the waters of Gosong Tiaka. The highest number of species for phytoplankton and zooplankton groups were found in the Bacillariophyceae class (9 species) and Copepoda class (3 species), respectively. While the highest abundance of phytoplankton and zooplankton was obtained in Chaetocerus sp. (Bacillariophyceae class) and Temora sp. (Copepoda class), respectively. This indicates that plankton from the Bacillariophyceae and copepod classes play a very important role in the study site. Based on the ecological index assessment, plankton diversity is in the medium assessment range, which means that the condition of the aquatic environment in the water location is in the medium assessment range (not under heavy environmental pressure). The plankton community in these waters is in a stable condition, indicated by the absence of dominating species.